Self psychology and psychosis : the development of the self during intensive psychotherapy of schizophrenia and other psychoses /: the development of the self during intensive psychotherapy of schizophrenia and other psychoses. (2015) - Garfield, David A. S; Steinman, Ira
No abstract available